Cascade imination, Buchwald–Hartwig cross coupling and cycloaddition reaction: synthesis of pyrido[2, 3-d]pyrimidines. Issue 30 (2nd March 2015) - Saikia, Pallabi; Sharma, Gitarthi; Gogoi, Sanjib; Boruah, Romesh C.
Abstract : A new approach for the synthesis of pyrido[2, 3- d ]pyrimidines via cascade imination/Buchwald–Hartwig cross coupling/cycloaddition reactions is described. Abstract : A novel and efficient palladium catalyzed method was developed for the synthesis of wide range of pyrido[2, 3- d ]pyrimidines, using readily available β-bromovinyl/aryl aldehydes and 6-amino-1, 3-dialkyluracils as the starting materials with good yields. This reaction proceeds via cascade imination/Buchwald–Hartwig cross coupling/cycloaddition reactions under microwave irradiation and solvent free conditions.